Influence of concomitant coronary artery bypass graft on outcome of surgery of the ascending aorta/arch. Issue 2 (16th August 2006) - Narayan, P; Rogers, C A; Caputo, M; Angelini, G D; Bryan, A J
Abstract : Background: Surgery of the ascending aorta with or without arch is being performed in an increasingly elderly population with risks of coexisting coronary artery disease. Aim: To define specific groups requiring coronary artery bypass graft (CABG) and to analyse the influence of concomitant CABG on outcome. Design: Over a 10-year period in a single institution, 296 consecutive procedures on the ascending aorta with or without arch were carried out in 291 patients. CABG was required in 42 (14.2%) procedures. In 24 (57%) patients, CABG was planned preoperatively and in 18 (43%) patients, on a salvage basis. Results: In-hospital mortality for patients undergoing concomitant CABG was higher (21.4% v 11%, p<0.06). Adjusting for baseline and operative characteristics, this was attributable to operative priority, and was not a consequence of concomitant CABG (adjusted OR 0.30, 95% CI 1.1 to 8.31; p = 0.48). However, in-hospital mortality was significantly higher when CABG was performed as salvage rather than as a planned procedure (38.9% v 8.9%, p = 0.025), and this difference remained after adjusting for confounding variables (adjusted OR 16.2, 95% CI 1.03 to >200; p = 0.047). The 3-year survival was significantly lower with concomitant CABG (59% v 81.9%, p<0.001). Conclusions: In association with surgery of the ascending aorta with or without arch planned concomitant CABG did not entail any added operative risk. However, salvage CABG, which occurred almost exclusively in association with emergency cases, was associated with a higher early mortality. Patients needing concomitant CABG had worse survival at 3 years compared with those requiring isolated surgery of the ascending aorta with or without arch.